Exploratory analysis on the association of dietary live microbe and non-dietary prebiotic/probiotic intake with serum cotinine levels in the general adult population - Lin, Shanhong; Zhu, Ning; Zhu, Yujing; Mao, Haiping; Zhang, Shengmin (Frontiers in Nutrition, 2024)
Background: Previous research has indicated the potential involvement of the microbiota in smoking-related processes. The present study seeks to examine the relationship between dietary live microbes, as well as probiotic or prebiotic consumption, and serum cotinine levels.Methods: This study used data from the National Health and Nutrition Examination Survey 1999-2018. Dietary intake information and probiotic/prebiotic intake data was collected through selfreported questionnaires. Participants were stratified into low, medium, and high intake groups according to their consumption of foods with varying microbial content. Multiple linear models were applied to explore the relationships of dietary live microbes, probiotic or prebiotic use with the serum cotinine level.Results: A total of 42,000 eligible participants were included in the final analysis. The weighted median serum cotinine level was 0.05 (0.01, 10.90) ng/ml. Participants with low, medium, and high dietary microbe intake represented 35.4%, 43.6%, and 21.0% of the cohort, respectively. Furthermore, participants were stratified into three groups based on their overall consumption of foods with variable microbe contents. The association between dietary live microbe intake and serum cotinine levels remained robust across all models, with medium intake as the reference (Model 2: β=-0.14, 95% CI: -0.20, -0.07; High: β=-0.31, 95% CI: -0.39, -0.22). Moreover, both prebiotic and probiotic use exhibited an inverse relationship with serum cotinine levels (Prebiotic: β=-0.19, 95% CI: -0.37, -0.01; Probiotic: β=-0.47, 95% CI: -0.64, -0.30). Subgroup analyses revealed no discernible interactions between dietary live microbe, prebiotic, probiotic use, and serum cotinine levels.Our findings suggest a negative correlation between dietary live microbe intake, as well as non-dietary prebiotic/probiotic consumption, and serum cotinine levels.